Multimodal Music Perception Engages Motor Prediction: A TMS Study - Gordon, Chelsea L.; Iacoboni, Marco; Balasubramaniam, Ramesh (Frontiers in Neuroscience, 2018)
Corticospinal excitability (CSE) in humans measured with Transcranial Magnetic Stimulation (TMS) is generally increased by the perception of other people’s actions. This perception can be unimodal (visual or auditory) or multimodal (visual and auditory). The increase in TMS-measured CSE is typically prominent for muscles involved in the perceived action (muscle specificity). There are two main classes of accounts for this phenomenon. One suggests that the motor system mirrors the actions that the observer perceives (the resonance account). The other suggests that the motor system predicts the actions that the observer perceives (the predictive account). To test these accounts (which need not be mutually exclusive), subjects were presented with four versions of three-note piano sequences: sound only, sight only, audiovisual, and audiovisual with sound lagging behind (the prediction violation condition). CSE was measured in two hand muscles used to play the notes. CSE increased reliably in one muscle only for the prediction violation condition, in line with the predictive account, while the other muscle demonstrated CSE increase for all conditions, in line with the resonance account. This finding supports both predictive coding accounts as well as resonance accounts of motor facilitation during action perception.